Negative Pressure Wound Therapy in Conjunction With Artificial Dermis for Burned Hand Reconstruction. (February 2021) - Ou, Kuang-Ling; Tzeng, Yuan-Sheng; Liu, Hung-Hui; Wu, Chien-Ju; Chen, Chun-Yu; Chou, Yu-Yu; Hsu, Kuo-Feng; Wang, Chih-Hsin; Dai, Niann-Tzyy; Chang, Chun-Kai
Abstract : Introduction: Proper wound care along with the use of skin grafts over deep burn wounds has been the standard treatment. However, the goal in burn wound care has shifted from achieving a satisfactory survival rate to improving long-term form and function of the healed wound, which is sometimes hindered by scar contracture. This has prompted surgeons to find alternative ways to treat burn wounds without compromising function. Among burn cases, hand injuries are the most problematic when it comes to delicate function recovery. Methods: This study presents the results of conjunctive use of a bilayer artificial dermis, negative pressure wound therapy, and split-thickness skin grafts for grafting over acute burn wounds and scar-releasing defects after severe hand burns. Results: Three months after the operation, the scar was soft and pliable, the aesthetic outcome was good, and the patients gained much improvement in hand function and quality oflife. Conclusions: The combined technique achieved a good scar quality and aesthetic effect on burned hands as well as excellent functional outcome, which resulted in major improvements and an independent life for the patient.